Nanoplastics as emerging cardiovascular hazards: a narrative review of current evidence - Gbolahan Olatunji; Emmanuel Kokori; Ikponmwosa Jude Ogieuhi; Udojike I. Chidinma; Oluwatobi Omoworare; Doyin Olatunji; Ajekiigbe Victor Oluwatomiwa; Oyebiyi Babajide Oyewale; Omotade Omolade Dorcas; Varisha Zuhair; Bonu Innocent Shu; Anthony Chidera Stanley; et al. (SpringerOpen, 2024)
Abstract Background Nanoplastics (NPs) have emerged as significant environmental pollutants, raising concerns due to their ubiquitous presence and potential adverse effects on human health. The migration and fate of NPs in the environment are subjects of intense study, with human exposure pathways expanding through ingestion, inhalation, and dermal contact. Body Studies indicate that NPs can infiltrate the cardiovascular system, potentially causing adverse effects. Mechanistic insights from in vitro and animal studies suggest that oxidative stress, inflammation, apoptosis, and mitochondrial dysfunction contribute to nanoplastic-induced cardiovascular toxicity. Animal models demonstrate altered heart rate, myocardial fibrosis, and dysfunction following NPs exposure, with specific adverse effects observed in cardiac valves and mitochondrial structure. Clinical studies provide further evidence of NPs accumulation in cardiovascular tissues, with implications for cardiovascular pathologies such as atherosclerosis and myocardial infarction. Notably, patients with higher levels of nanoplastics in carotid plaque exhibit an increased risk of adverse cardiovascular outcomes. Conclusion However, challenges in studying nanoplastics persist, including methodological limitations, ethical considerations, and the need for standardized detection methods. Addressing these challenges requires interdisciplinary collaboration, innovative research approaches, and robust regulatory measures to mitigate NPs pollution and protect cardiovascular health.